2021
DOI: 10.3390/ani11072077
|View full text |Cite
|
Sign up to set email alerts
|

The Goat as a Risk Factor for Parasitic Infections in Ovine Flocks

Abstract: Small ruminants in northwestern Spain are frequently managed in mixed flocks. Sheep–goat joint management has not been considered a risk factor for parasite infection, so the main objective of this study was to establish if mixed management with goats supposes a risk factor for parasitic infections in ovine flocks. Two thousand and ninety-three sheep were sampled from 74 commercial meat ovine flocks for diagnostic of the main parasites. Goat contact was a risk factor for sheep to be infected by protostrongylid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 14 publications
9
2
1
Order By: Relevance
“…Despite this limitation, it can, however, be assumed that the prevalence of rumen flukes in goats is indeed very low in Germany. The observed difference in prevalence between goats and sheep, as well as cattle, is also reflected in previous studies [ 10 , 38 , 39 , 42 , 50 ]. A possible explanation is the different feeding behavior of the three ruminant species.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Despite this limitation, it can, however, be assumed that the prevalence of rumen flukes in goats is indeed very low in Germany. The observed difference in prevalence between goats and sheep, as well as cattle, is also reflected in previous studies [ 10 , 38 , 39 , 42 , 50 ]. A possible explanation is the different feeding behavior of the three ruminant species.…”
Section: Discussionsupporting
confidence: 83%
“…It was also below the prevalence of 5.5% recently identified in German cattle by our research group using identical methods (Lower Saxony: 10.9%, Bavaria: 4.4%) [ 6 ]. In comparison to cattle, a lower rumen fluke prevalence in small ruminants has also been observed in most other European studies which simultaneously studied or conducted comparable studies in all these species [ 10 , 38 , 39 , 42 , 44 , 54 , 65 ]. The detected prevalence of patent F. hepatica infections was similar to the percentages of positive farms or samples identified in previous German studies [ 41 , 48 , 50 ], despite considerable differences in farm numbers, representation, and farm or sample selection.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…The higher cumulative FOC of Eimeria spp. in goats compared to sheep aligns with previous studies [41], and contrasts with other authors where the opposite situation was observed [24]. As anticipated, the development of robust immunity with aging resulted in a lower cumulative FOC observed in our study in adults compared to pre-adults in both species, which is consistent with previous studies [5,24,36].…”
Section: Cumulative Fecal Oocyst/egg Countssupporting
confidence: 92%